Memory-related neurophysiological mechanisms in the hippocampus underlying stress susceptibility - Nahoko Kuga; Takuya Sasaki (Neuroscience Research)
Stress-induced psychiatric symptoms, such as increased anxiety, decreased sociality, and depression, differ considerably across individuals. The cognitive model of depression proposes that biased negative memory is a crucial determinant in the development of mental stress-induced disorders. Accumulating evidence from both clinical and animal studies has demonstrated that such biased memory processing could be triggered by the hippocampus, a region well known to be involved in declarative memories. This review mainly describes how memory-related neurophysiological mechanisms in the hippocampus and their interactions with other related brain regions are involved in the regulation of stress susceptibility and discusses potential interventions to prevent and treat stress-related psychiatric symptoms. Further neurophysiological insights based on memory mechanisms are expected to devise personalized prevention and therapy to confer stress resilience.